Ladybird beetles Adalia bipunctata l. interaction with legume bean Phaseolus species is dependent on life needs - Rahaman, SK.M.; Aniszewski, T. (Penerbit Universiti Kebangsaan Malaysia, 2014)
Two-spots ladybird beetle (Adalia bipunctata) needs support from the plants species of legumes family common bean (Phaseolus vulgaris) and lima bean (P. lunatus) for completing their life circle. This interaction serves the need in terms of food, shelter, host-plant suitability and mutualism. This study investigated the interaction and different behavioural activity between the domestic ladybird and global plant species. Ladybird interacted with both bean species and showed intensive activity on the plants studied. Dualistic eating habits and their behavioral activity with Phaseolus species plants are new finding in this study. Results exhibited that, selected plant species are extremely important for Adalia bipunctata in context of their local ecosystems. It is suggested that interaction between domestic ladybird and global bean plants is extremely important for both types of organisms in the context of their local ecosystems.